Перспективный блочный симметричный шифр, оптимизированный для аппаратной реализации - Олейников, Р. В.; Киянчук, Р. И. (ХНУРЭ, 2011)
Confidentiality of data transfer in modern information and telecommunication systems is usually provided by application of symmetric block ciphers. At the same time widely used block ciphers are generally designed for software implementation (AES) or special-purpose hardware modules (DES, TripleDES). Their system-on-a-chip implementations with strict constraints to the number of logic gates and energy consumption are quite ineffective. Consequently, such systems require a new generation cryptographic algorithms. Our paper examines requirements for symmetric block ciphers designed for lightweight hardware implementations, describes the perspective cipher specifications, its properties and comparison with already existing ciphers.
Keywords: обработка конфиденциальной информации; конфиденциальная информация